1996
DOI: 10.1128/jb.178.16.4854-4860.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of nanB, a second Streptococcus pneumoniae neuraminidase gene, and purification of the NanB enzyme from recombinant Escherichia coli

Abstract: Streptococcus pneumoniae is believed to produce more than one form of neuraminidase, but there has been uncertainty as to whether this is due to posttranslational modification of a single gene product or the existence of more than one neuraminidase-encoding gene. Only one stable pneumococcal neuraminidase gene (designated nanA) has been described. In the present study, we isolated and characterized a second neuraminidase gene (designated nanB), which is located close to nanA on the pneumococcal chromosome (app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 36 publications
2
134
1
Order By: Relevance
“…These results could be explained as follows: (i) modification of the enzyme might occur in T. forsythensis and not in E. coli, (ii) other sialidases might exist in this bacterium. Streptococcus pneumoniae expresses two distinct sialidases (neuraminidases), NanA (Berry et al, 1988), which is cellassociated, and NanB (Berry et al, 1996). These results revealed that the purified sample from pHI-1 : 1 might be identical to that from the original bacterium T. forsythensis.…”
Section: Discussionmentioning
confidence: 61%
“…These results could be explained as follows: (i) modification of the enzyme might occur in T. forsythensis and not in E. coli, (ii) other sialidases might exist in this bacterium. Streptococcus pneumoniae expresses two distinct sialidases (neuraminidases), NanA (Berry et al, 1988), which is cellassociated, and NanB (Berry et al, 1996). These results revealed that the purified sample from pHI-1 : 1 might be identical to that from the original bacterium T. forsythensis.…”
Section: Discussionmentioning
confidence: 61%
“…When the central parts of IS200 elements amplified by PCR from strains of E. coli and Salmonella were sequenced, their analysis showed that IS200 must have been present in the common ancestor of the two species, and that it had not been transferred between them since their divergence. This was in contrast to the IS1 element, which was found to be isogenic in both species, reflecting recent horizontal transfer (Bisercic & Ochman, 1993a). Random mutagenesis with TnlO followed by genetic mapping of those transposons which were linked to IS200 insertion sites showed that six IS200 copies in S .…”
Section: Introductionmentioning
confidence: 73%
“…The original sequence for IS200 was 708 bp in length but since an additional ' C' is found at nucleotide 1524, this would bring the length of the element to 711 bp. The additional 'C' found at this position has also been reported to be present in the IS200 elements of two Salmonella strains from the SARA reference collection (Bisercic & Ochman, 1993a), and therefore probably represents the ancestral sequence of the element. Given the available evidence it cannot be decided whether the occupied or unoccupied insertion site is ancestral.…”
Section: Comparison Of An Occupied and Unoccupied Is200 Insertion Sitementioning
confidence: 99%
See 2 more Smart Citations